The effectiveness of community health workers in reducing blood pressure in South Asia - Long, Molly U. (International Journal Of Community Medicine And Public Health, 2025)
Globally, one-third of adults have hypertension, the leading modifiable risk factor for the leading causes of death worldwide- ischemic heart disease and stroke. In South Asia, where the burden of hypertension is high and the number of physicians and nurses is insufficient for the population, community health workers (CHWs) are one potential means to fill this gap in care. This literature review analyzes evidence of the effectiveness of utilizing CHWs to reduce systolic blood pressure in the South Asian context. Searches for relevant articles in South Asia were performed in PubMed and Cochrane databases. The database searches led to the retrieval of 66 articles, of which 5 studies were selected for this review. A significant reduction in systolic blood pressure (ranging from 5 to 8.9 mmHg decrease and/or improved BP control in the population, OR 1.6) was found in CHW interventions targeting hypertensive adults in the community. The results demonstrate that CHW interventions in South Asia can be effective in significantly reducing systolic blood pressure in hypertensive adults in a community. In an area of the world with a shortage of physicians and nurses, these findings indicate that CHWs can be utilized to effectively reduce systolic blood pressure in hypertensive patients in South Asian communities. This has great potential for long-term reduction of ischemic heart disease and stroke in this region of the world.